Aplikasi Dan Dosis Pupuk Majemuk Npk (15-15-15) Terhadap Hasil Tomat Dalam Sistem Tumpangsari Dengan Kubis Dan Petsai - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT A factorial randomized block design with three replicates was used to evaluate of total yield of tomato and land equivalent ratio (LER) in intercropping system with cabbage and chinese cabbage. Treatments consisted of three factors. First factor consisted of three intercropping systems, i.e. tomato monoculture, tomato with chinese cabbage, and tomato with cabbage. The second factor consisted of two levels of NPK (15-15-15) rate: 900 kg per ha and (B2) 1000 kg per ha. The third factor consisted of two levels of application date of NPK (15-15-15) fertilizer: at planting date of cabbage and chinese cabbage and at planting date of tomato. The results showed that there was no interaction effects among intercropping system, dosage of NPK (15-15-15) fertilizer and application date of NPK (15-15-15) fertilizer on total yield of tomato. There were three kinds of treatments that have the same effect on total yield production of tomato as main crop and chinese cabbage or cabbage as intercrops. However, intercropping system between tomato and chinese cabbage or tomato and cabbage gave higher values of Land Equivalent Ratio (LER) and economically profitable in comparation with that of tomato planted monoculturally. Keywords: compound fertilizer, intercropping, tomato, Brassica oleracea L., Brassica pekinensis L. INTISARI Tujuan dari penelitian ini untuk mengetahui basil total tomat dan Nilai Kesetaraan Lahan (Land Equivalence Ratio, LER) dalam sistem tumpangsari tomat dengan kubis dan petsai. Rancangan yang digunakan yaitu Rancangan Acak Kelompok Faktorial dengan tiga faktor dan diulang tiga kali. Faktor pertama adalah sistem pertanaman: tomat monokultur, tomat dengan petsai, dan tomat dengan kubis. Faktor kedua adalah dosis pupuk NPK (15-15-15), yaitu 900 kg per ha dan 1000 kg per ha. Faktor ketiga adalah waktu aplikasi pupuk NPK (15-15-15) yaitu pupuk diberikan pada saat tanam kubis dan petsai serta pupuk diberikan pada saat tanam tomat. Hasil penelitian menunjukkan bahwa tidak ada pengaruh interaksi di antara sistem tumpangsari, dosis pupuk NPK (15-15-15), dan waktu aplikasi pupuk NPK (15-15-15) terhadap hasil total tomat. Ketiga macam perlakuan mempunyai pengaruh yang sama terhadap hasil tomat sebagai tanaman utama dan petsai atau kubis sebagai tanaman sela. Sistem tumpangsari tomat dan petsai atau tomat dan kubis memberikan nilai kesetaraan lahan yang tinggi dan memberikan keuntungan bila dibanding dengan sistem tanam tunggal tomat.